Association of traffic volume and leukocyte telomere length of Malaysian populations living in urban and rural areas - Samer Al-Battawi; Yu Bin Ho; Mohd Talib Latif; Vivien How; Haris Hafizal Bin Abd Hamid; Sarah Hameed; Karuppiah Thilakavathy (Environmental Chemistry and Ecotoxicology)
Telomeres are repetitive sequences (5′-TTAGGG-3′) of deoxyribonucleic acid (DNA) at the ends of eukaryotic chromosomes and play a critical role in maintaining genomic stability. Shortened telomeres are linked to cellular senescence and apoptosis with environmental factors such as traffic volume pollution potentially influencing telomere length. This study examined the variation in leukocyte telomere length (LTL) among adults living in high- and low-traffic areas in Malaysia. A cross-sectional analysis was conducted on 101 adults from a high-traffic area, Kuala Lumpur and 101 adults from Hulu Langat, a low-traffic area, to assess the relationship between exposure to traffic volume and LTL. Healthy, non-smoking, non-alcoholic participants who had resided and worked in their respective locations for the past five years were selected. LTL was measured using the quantitative polymerase chain reaction (qPCR) method from peripheral blood samples, revealing that participants from the high-traffic area had significantly shorter mean LTL (0.77 ± 0.23) than those participants from the low-traffic area (1.09 ± 0.07) (p < 0.001). Notably, there is a strong inverse relationship between heavy traffic exposure and LTL, as LTL decreased by 0.38 units [(95 %CI: 0.26, 0.5), p = 0.01] and 0.16 units [(95 %CI: −0.16, 0.19), p = 0.04] for each increase in a single light vehicle and heavy vehicle, respectively. Individual covariates, outdoor jobs, intake of grilled food, indoor grilling, and passive smoking were also negatively associated with LTL. These findings suggest that high traffic volume may contribute to reduced telomere length and has broader implications on public health.